Harmoni Masyarakat Tradisi dalam Kerangka Multikuluralisme - Mahardhani, Ardhana Januar; Cahyono, Hadi (Asketik: Jurnal Agama dan Perubahan Sosial, 2017)
Society in this era can be said to the modern society with anything life sufficiency that is very easy to get, but there are still many societies that have not been released with their tradition that has been happened a long time before they are birth. Existence and continuance of activities of the traditional element, such as in Java culture which is known as count the day activity before the wedding held, salvation whether for a baby born or dead, and home construction, precisely these activities that bring diversity in multiculturalism element. Multiculturalism itself is the recognition that there are different cultures but they are still can live and develop within a similar environment without loss on either side. That thing becomes the basis of this article's writing. Trying to watch the difference is a natural thing in the multiculturalism framework.